THE RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH HYPERTROPHIC OBSTRUCTIVE CARDIOMYOPATHY AS A RISK FACTOR OF SUDDEN CARDIAC DEATH - Rudenko, K.V.; Lazoryshynets, V.V.; Trembovetska, O.M.; Nevmerzhytska, L.O.; Tregubova, M.O.; Danchenko, P.A. (World of Medicine and Biology, 2020)
The study includes 250 consecutive symptomatic patients with hypertrophic obstructive cardiomyopathy who underwent surgical extended myectomy, resection of anomalous chordal structures, mobilization of the papillary muscles and plication of the anterior mitral valve leaflet. The purpose of the study is to analyze the effectiveness of this technique and the immediate results of surgical correction. The results showed a statistically significant decrease of systolic pressure gradient on the left ventricular outflow tract, mitral regurgitation and an improvement in NYHA functional class. Sudden cardiac death (SCD) risk stratification was performed in 235 patients. The results of the study showed that the multi-stage correction allows to influence all links of pathological manifestation of the disease, but the question is how to predict the risk of SCD in already operated patients and how to protect them from life-threatening events?
Keywords: hypertrophic cardiomyopathy; extended septal myectomy; surgical correction; sudden cardiac death